Fourteen new species, one new genus, and eleven new country or state records for New World Lamiinae (Coleoptera, Cerambycidae) - Martins, Ubirajara R.; Santos-Silva, Antonio; Galileo, Maria Helena M. (Zootaxa, 2015)
Fourteen new species and one new genus are described from the New World in Lamiinae (Coleoptera: Cerambycidae): Bisaltes (Bisaltes) lingafelteri sp. nov., Trestonia skelleyi sp. nov. and Psapharochrus langeri sp. nov. from Bolivia; Eupogonius azteca sp. nov., Aegomorphus mexicanus sp. nov., Lamacoscylus albatus sp. nov., Lamacoscylus obscurus sp. nov. and Piruanycha wappesi sp. nov. from Mexico; Dolichestola egeri sp. nov. and Wappesellus cavus gen. nov., sp. nov. from Brazil (Rondônia); Scleronotus virgatus sp. nov. from Venezuela; Oreodera casariae sp. nov. from Panama; Alampyris bicolor sp. nov. from Costa Rica; and Emphytoeciosoma flava sp. nov. from Peru. Additionally, eleven new country/state records are established in Lamiinae: three for Peru; three for Bolivia; one for Mexico; one for Uruguay; and two for Brazil (Rondônia) (state records). Bisaltes (Bisaltes) lingafelteri, Eupogonius azteca, Aegomorphus mexicanus, Lamacoscylus albatus, Lamacoscylus obscurus, Piruanycha wappesi, Scleronotus virgatus, Alampyris bicolor, Emphytoeciosoma flava and Wappesellus are included in new or known keys.